Komunikasi Antarbudaya Dalam Proses Asimilasi Suku Tapanuli Dan Suku Minang Di Desa Durian Kadap Kabupaten Pasaman - Riska Hannum; Darul Ilmi (Universitas Pahlawan Tuanku Tambusai, 2023)
This study uses qualitative data analysis methods that emphasize certain cases that occur in the object of analysis. This method uses descriptive analysis to analyze the data. The informants in this study were three married couples in mixed marriages of the Tapanuli and Minang tribes in Durian Kadap Village, Pasaman Regency. Meanwhile, to analyze the collected data, the author used data reduction, data presentation and conclusions. The result of the research show that the process of intercultural communication can be well established and effective between the three pairs. Mixed marriages occur when the fat of ethnocentrism is removed. The way to overcome ethnocentrism is to be open and willing to learn about other people’s cultures. All informants have tried to respect and appreciate, acknowledge cultural differences in marriage and follow the culture of their partners. There is a change in perspective (religion, values and behavior) based on the head of the family. The direction of adaptation and assimilation (assimilation) is related to the heads of families from both the Minang and Tapanuli tribes. Domination of ethnicity and culture by the Minang ethnic group also occurs in the Tapanuli ethnic group. Keywords: Communication Intercultural, Assimilation Marriage and Ethnocentrism